The Impact of Banks Loan to SMEs on Manufacturing Output in Nigeria - Ifeakachukwu, NWOSA Philip (Journal of Social and Development Sciences, 2013)
This study examines the impact of banks loan to SMEs on manufacturing output in Nigeria for the period spanning 1992 to 2010. The study employed an error correction modeling technique and observed that banks loan to the SME sector had insignificant impact on manufacturing output both in the long and short run. Based on the findings, the study recommended the need for greater deliberation and conscious effort by the government in ensuring that loans are given to ultimate users. There is also the need for moderation of collaterals and interest rate attached to banks loan to SMEs, to make it more attractive to stakeholders in the SMEs sector.